1955
DOI: 10.1099/00221287-13-3-461
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies on Small-colony Variants of Escherichia coli K-12

Abstract: SUMMARY: Stable small-colony variants of Escherichia coli K-12 and several of its auxotrophs were isolated by treatment of cultures with copper sulphate solutions. These variants did not show any associated changes in nutritional, fermentative or serological characters. The small-colony forms showed normal recombining character in two instances, but in one variant the F -form showed a lower recombination rate and atypical transfer of markers. However, when rendered F + this variant behaved in a manner analogou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1957
1957
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Previous work has shown that a stable smallcolony variant of Escherichia coli appears in a population of organisms exposed to copper (Weed and Longfellow, 1954). Similar findings were reported by Clowes and Rowley (1955) and Hirsch (1961). Associated with the changes in colonial morphology are differences in metabolism, ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) content, and resistance to ultraviolet irradiation.…”
supporting
confidence: 85%
“…Previous work has shown that a stable smallcolony variant of Escherichia coli appears in a population of organisms exposed to copper (Weed and Longfellow, 1954). Similar findings were reported by Clowes and Rowley (1955) and Hirsch (1961). Associated with the changes in colonial morphology are differences in metabolism, ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) content, and resistance to ultraviolet irradiation.…”
supporting
confidence: 85%
“…The rapidly growing Salmonella developed well in a medium composed of glucose, citrate, ammonium nitrogen and mineral salts, whereas the slowly growing strains required amino acids for growth and in some instances also B-vitamins. Recently Clowes and Rowley (1955) suggested that permeability may be the limiting factor in the growth of small colony variants of Escherichia coli. We have experiments now under way to determine to what extent the metabolism of amino acids and permeability influence the growth rates of S. pullorum and other Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Among the genetically stable variants of SC, most are metabolic mutants, defective either in the electron transport chain or in the thymidine biosynthesis pathway (14). Early studies have found nonpathogenic E. coli to unstably form small colonies under prolonged exposure to chemicals like phenol or anthraquinone (37,38). Under our experimental framework, we observed that E. coli diversifies into stable, regulatory mutants which phenotypically produce small colonies with enhanced stress tolerance after 3 weeks of incubation in rich spent medium.…”
Section: Discussionmentioning
confidence: 72%